APLIKASI ENZIM TRANSGLUTAMINASE DAN UBI UNGU PADA YOU-SIS (YOGURT- SOSIS) SEBAGAI UPAYA PENCEGAHAN STUNTING DAN KETAHANAN PANGAN DI DESA PANDAK - Irfan Fadhlurrohman; Deni Setiadi; Indra Sugiharto; Abdul Malik Firdaus; Hasan Muhammad Yusuf; Lia Andeyani; Muhammad Raffi Akbar Yustisio; Rifki Ramadhan Nur Solehan; Audina Az-Zahra; Nafareza Belvayuna; Rafli Fauziyanto Johan (Jurnal Abdi Insani, 2026)
Stunting remains a major nutritional problem in Indonesia, particularly in rural areas with limited access to nutritious food and low consumption of animal protein. Pandak Village has local food potential such as milk, chicken meat, and purple sweet potato, but these resources have not been optimally utilized into value-added products. In addition, limited nutrition knowledge and food processing skills hinder adequate dietary intake. Therefore, an applicable local food-based innovation is needed. This program aimed to improve community knowledge, skills, and independence through the YOU-SIS (Yogurt & Sausage) innovation based on transglutaminase enzyme and purple sweet potato to support stunting prevention and food security. The methods included education sessions, hands-on training (learning by doing), and evaluation using pre-test and post-test. Activities were conducted participatively, involving a women farmer group as the main partner in technology transfer. The results showed significant improvements in participants’ knowledge and skills, with average increases of 49% in sausage processing and 57% in yogurt processing. Transglutaminase improved sausage texture and elasticity, while purple sweet potato enhanced color, aroma, texture, and functional value due to fiber and antioxidant content. The YOU-SIS product demonstrated good sensory acceptability. This innovation also increased the utilization of local food resources and community nutrition awareness. Overall, this program is effective as a functional food-based intervention model to support stunting prevention and community food security.